Application of Fluorine-18-Deoxyglucose Positron Emission Tomography and Gallium Scan for Assessment in a Patient With Adult-Onset Still’s Disease - Jing-Uei HOU; Shih-Chuan TSAI; Wan-Yu LIN (Archives of Rheumatology, 2016)
A 53-year-old female patient suffered from pain in almost her entire body, particularly the joints. Chest computed tomography revealed multiple lymphadenopathies over cervical, mediastinal, and axillary areas. A fluorine-18-deoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) revealed increased FDG uptake in many lymph nodes and the spleen. Lymphoma was suspected. However, the result of a biopsy showed no malignancy, and the gallium-67 citrate scan showed no gallium-avid tumor throughout the whole body. Adult-onset Still’s disease was diagnosed and the patient responded well to steroid therapy. The follow-up PET/CT six months later showed complete remission of the FDG-avid lesions seen in the previous PET/CT. Our study suggests that FDG PET/CT combined with gallium-67 scan may be helpful in diagnosing patients with adult-onset Still’s disease. In addition, the use of FDG PET/CT alone may be useful for the evaluation of disease distribution, disease activity, and therapeutic response.